Strategi Guru Pendidikan Agama Islam dalam Menanamkan Toleransi Siswa di SMP Negeri 19 Kota Bengkulu - Sarah Pratama Putri; Edi Ansyah; Masrifa Handayani (GHAITSA : Islamic Education Journal, 2021)
This research is motivated by a reality about the importance of increasing the tolerance of students of different religions. The emergence of tolerance in schools requires concrete efforts from all parties in the school, one of which is a religious teacher in classroom learning. On this basis, the formulation of the problem in this study is how the strategy of Islamic Religious Education teachers in increasing student tolerance at SMP Negeri 19 Bengkulu City and what factors influence teacher strategies in increasing student tolerance at SMP Negeri 19 Bengkulu City. The purpose of this study is first, to find out the strategy of Islamic Religious Education teachers in increasing student tolerance at SMP Negeri 19 Bengkulu City. Second, knowing the factors that influence the teacher's strategy in increasing student tolerance at SMP Negeri 19 Bengkulu City. This research is a field research (field research) while the method used is descriptive. Informants in this study were principals, teachers and students. Data collection techniques are observation, interviews and documentation. Based on the presentation and discussion of research data, it can be concluded that first, the strategy of Islamic Religious Education teachers in increasing student tolerance at SMP Negeri 19 Bengkulu City is by instilling the values of cooperation, solidarity, tolerance, responsibility and compassion in students. With the instillation of these values, it has strengthened students' sense of tolerance towards fellow human beings. In increasing student tolerance in the classroom and outside the classroom, it has been carried out using exemplary methods, advice, approaches and habituation. Second, the supporting factors of Islamic religious education teachers in increasing student tolerance are reflected through the cohesiveness of the school, strong cooperation between the school and the parents of students. While the inhibiting factors are the good environment, the family that is not conducive and the spectacle in the mass media that is not educational.